Mirroring the Parking Target: An Optimal-Control-Based Parking Motion Planner With Strengthened Parking Reliability and Faster Parking Completion - Hu, Jia; Feng, Yongwei; Li, Shuoyuan; Wang, Haoran; So, Jaehyun; Zheng, Junnian (IEEE Transactions on Intelligent Transportation Systems, 2024)
Automated Parking Assist (APA) systems are now facing great challenges with low adoption in applications, due to users' concerns about parking capability, reliability, and completion efficiency. To upgrade the conventional APA planners and enhance user's acceptance, this research proposes an optimal-control-based parking motion planner. Its highlight lies in its control logic: planning trajectories by mirroring the parking target. This method enables: i) parking capability in narrow spaces; ii) better parking reliability by expanding Operation Design Domain (ODD); iii) faster completion of parking process; iv) enhanced computational efficiency; v) universal to all types of parking. A comprehensive evaluation is conducted. Results demonstrate the proposed planner does enhance parking success rate by 40.6%, improve parking completion efficiency by 18.0%, and expand ODD by 86.1%. It shows its superiority in difficult parking cases, such as the parallel parking scenario and narrow spaces. Moreover, the average computation time of the proposed planner is 74 milliseconds. Results indicate that the proposed planner is ready for real-time commercial applications.
Keywords: Advanced driver assistance system; Advanced driver assistances; Automated parking; Collisions avoidance; Completion efficiencies; Driver-assistance systems; Motion planners; Motion-planning; Narrow spaces; Optimal controls; Advanced Driver Assistance Systems (ADAS); Automated parking; collision avoidance; motion planning; optimal control